Photoluminescence Properties of Poly (Ethylene Glycol) Passivated Carbon Dots from Cassava Peels - Permono Adi Putro; Liszulfah Roza; Isnaeni Isnaeni (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Carbon dots (C-dots) is a new type of luminescense nanoparticles that can be synthesized easily from natural sources, such as cassava peels. C-dots has been synthesized from cassava peels based green synthesis using low temperature. The surface of C-dots was passivated by poly(ethylene glycol) (PEG) with variations in volume from 0.5 ml, 1 ml, and 1.5 ml. Luminescense properties before and after passivasive with PEG characterized using photoluminescense (PL) and time resolved photoluminescence (TRPL) spectrophotometer. Peak wavelength spectrum of PL shows a red shift when 0.5 ml PEG was added. However, when the addition of PEG increases, peak wavelength spectrum of PL shows a blue shift. PL intensity decreased along with increasing of PEG volume. PL intensity influenced C-dots electron time decay linearly. C-dots electron time decay increased along with decreased of PL intensity. This results assigned potency that C-dots in water solution can be applied as bioimaging and metal ion and salt biosensing. however, it needs extra optical measurements to support our discovery.Keywords: cassava peels, C-dots, electron time decay, FL intensity, PEG